Biological Analysis of Leydig Cells-Conditioned Medium to Support Rat Bone Marrow Mesenchymal Stem Cells Differentiation - Kaiin, Ekayanti Mulyawati; Prasetyaningtyas, Wahono Esthi; Mohamad, Kusdiantoro; Djuwita, Ita; Yusuf, Tuty Laswardi; Setiadi, Mohamad Agus (Annales Bogorienses, 2018)
The developed Leydig cells-conditioned medium (LCM) contains bioactive materials secreted by Leydig cells in vitro. LCM was used to evaluate the ability of bone marrow mesenchymal stem cells differentiation. Bone marrow mesenchymal stem cells (1x 106 cell/ml) were cultured in : 1) DMEM supplemented with 10% NBCS as a control (M), 2) M supplemented with 10 ng/ml testosterone; 3) M supplemented with 50% LCM ; 4) M supplemented with 50% LCM and 2.5 IU/ml hCG. Bone marrow mesenchymal stem cells that were cultured with LCM has a positive reaction (57.4%) to histochemistry staining 3β-HSD and produced 1.87 ng/ml testosterone. Supplementation of hCG to LCM increased the positive number of Leydig cells and testosterone production by 74.6% and 12.33 ng/ml (P<0.05). It can be concluded that Leydig cells-conditioned medium can support differentiation of bone marrow mesenchymal stem cells into Leydig cells.